2019
DOI: 10.1080/13504851.2019.1707762
|View full text |Cite
|
Sign up to set email alerts
|

Does institutional quality condition the impact of financial stability transparency on financial stability?

Tim van Duuren,
Jakob de Haan,
Henk van Kerkhoff

Abstract: Using a fixed effects panel model on data for 110 countries over the period 2000-2011, we confirm previous findings that financial stability transparency increases the degree of financial stability in a country. However, our results also suggest that financial stability transparency is significantly negatively related to banks' non-performing loans only with low institutional quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The more financial institutions become illiquid, the more vulnerable they become, hence widening the gap in financial stability. This also confirms the findings of Van Duuren et al (2020), who identified NPLs as a key driver of financial stability among a sample of 110 countries. This finding is crucial and demands immediate and appropriate address as banking or financial systems with too many NPLs have detrimental economic and social impacts.…”
Section: Econometric Estimatessupporting
confidence: 89%
See 1 more Smart Citation
“…The more financial institutions become illiquid, the more vulnerable they become, hence widening the gap in financial stability. This also confirms the findings of Van Duuren et al (2020), who identified NPLs as a key driver of financial stability among a sample of 110 countries. This finding is crucial and demands immediate and appropriate address as banking or financial systems with too many NPLs have detrimental economic and social impacts.…”
Section: Econometric Estimatessupporting
confidence: 89%
“…Fahr and Fell (2017) stress that the financial stability gap can be closed through the use of macroprudential policies but not necessarily through a monetary policy. Also serving as the basis for this study, liquidity challenges with the financial institutions hinder their basic role in the economy and make them vulnerable to external shocks (Kulu et al, 2022b;Van Duuren et al, 2020;Almarzoqi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies such as Elfeituri (2022) have shown that institutional quality positively impacts bank stability. Besides Van Duuren et al (2020) using a fixed-effects panel model on data from 110 countries from 2000 to 2011, the study finds that previous findings suggest that financial transparency improves financial stability. However, the findings indicate that financial transparency is only negatively related to bad loans made by banks with low institutional quality.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 71%
“…These method has been used by the majority of studies listed in our literature review above, e.g. Chiuri et al (2002), Francis and Osborne (2012), Karmakar and Mok (2015), Aiyar et al (2016), Ben Naceur et al (2018), Tresierra and Reyes (2018), El Hourani and Mondello (2019), and van Duuren et al (2020). Note that the Fixed Effects method allows taking into consideration the bank-specific effects in the estimations by including individual intercepts for each cross-section.…”
Section: Methodology and Variables Specificationsmentioning
confidence: 99%
“…2. This is beside other aspects, mainly the association between institutional quality and banking stability (see for instance Essid et al , 2014; Silva and Chávez, 2015; van Duuren et al , 2020), and financial inclusion (see Bongomin et al , 2018), and financial development (see Hamadi and Awdeh, 2020). …”
Section: Notesmentioning
confidence: 98%